Chemical Properties and Micromorphology of Biochars Resulted from Pyrolysis of Agricultural Waste at Different Temperature - Nur Indah Mansyur; Eko Hanudin; Benito Heru Purwanto; Sri Nuryani Hidayah Utami (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Biochar quality is influenced by the type of its raw material and pyrolysis temperature. Nevertheless, the quality criteria of biochar as a nutrient carrier remain unanswered. This study aimed to find the chemical properties, micromorphology, and optimum pyrolysis temperature from various agricultural wastes to obtain good biochar as a nutrient carrier. This experiment was conducted at three level temperatures: 400, 500, and 600°C, and the raw materials were coconut shells, oil palm shells, and corn stalks. The chemical and physical properties of biochar were: pH-H2O, OC, CEC, total N, P, K, Mg, Ca, and Na, ash, functional groups, amorphous carbon, morphology, and SSA. The results show that the coconut shells and oil palm shells biochars contained high levels of N-total and the chain-C aromatic, and the pore structure was solid and regular. Corn stalks biochar containing ash is high, and C-aromatic is low and fragile. Increased temperature of pyrolysis produced well-crystallized minerals. It is concluded that 500°C is the optimum temperature for oil palm shells pyrolysis resulting in biochar with the highest C-aromatic structure and arrangement of pores which are strong, regular and uniform, and high stability, but the nutrient content was low.